The effect of fumaric acid-sodium bicarbonate on the green tea effervescent granule’s quality made by dry granulation - Agatha Budi Susiani Lestari; Maria Yuli Trisusilawati (Indonesian Journal of Pharmacy, 2010)
Tea plant (Camellia sinensis L.) had been known contains epigallocathecin gallate  (EGCG)  that  can  be  used  to  maintain  the  healthy.  In  this  research,  the green  tea  will  be  tried  to  be  formulated  in  effervescent  dosage  form,  with  the focus  on  the  effect  among  fumaric  acid,  sodium  bicarbonate,  or  the  interaction between  fumaric  acid  and  sodium  bicarbonate  on  the  green  tea  extract effervescent  granule’s  physical  properties,  that  made  by  dry  granulation method.  Physical  properties  of  effervescent  granule that  been  study  were moisture  content,  flow  rate,  disintegration  time,  and  pH  of  the  solution.  The result showed that sodium bicarbonate was dominant in determining pH, granule flow  rate  and  moisture  content  of  granule,  whereas  fumaric  acid  dominant  in disintegration time of effervescent granule.Key words: green tea, fumaric acid, effervescent granule, dry granulation